2012
DOI: 10.4088/jcp.10m06628
|View full text |Cite
|
Sign up to set email alerts
|

Lifespan Persistence of ADHD

Abstract: The ADHD Life Transition Model seeks to improve care for individuals with ADHD by (1) underscoring that ADHD persists beyond childhood in at least two-thirds of patients, (2) raising awareness of the need to approach ADHD from a chronic illness standpoint, and (3) increasing mental health professionals' diligence in symptom recognition and management of ADHD across developmental phases from childhood through adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(72 citation statements)
references
References 111 publications
0
54
0
2
Order By: Relevance
“…Other studies have revealed higher levels of discontinuation in adults [37–40]. Continuity of drug treatment may be compromised when patients transition from the adolescent health and social care systems to the adult system [10, 41], and some physicians may be reluctant to prescribe ADHD drugs to adults [1, 2, 4, 8]. We observed a higher proportion of early discontinuation and drug switching among users who initiated treatment with atomoxetine than those initiating treatment with methylphenidate.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have revealed higher levels of discontinuation in adults [37–40]. Continuity of drug treatment may be compromised when patients transition from the adolescent health and social care systems to the adult system [10, 41], and some physicians may be reluctant to prescribe ADHD drugs to adults [1, 2, 4, 8]. We observed a higher proportion of early discontinuation and drug switching among users who initiated treatment with atomoxetine than those initiating treatment with methylphenidate.…”
Section: Discussionmentioning
confidence: 99%
“…DSM-5 Task Force., 2013). ADHD persists into adulthood in up to 65% of cases (Faraone et al, 2006; Simon et al, 2009; Turgay et al, 2012), affects the ability to gain and maintain employment (Kessler et al, 2009; Kupper et al, 2012), and is associated with an increased risk for substance abuse (Wilens et al, 1995; Upadhyaya, 2008; Groenman et al, 2013), obesity (Cortese et al, 2008; Nazar et al, 2012; Albayrak et al, 2013; Nazar et al, 2014), workplace injuries (Swensen et al, 2004; Breslin and Pole, 2009; Hodgkins et al, 2011), and traffic accidents (Barkley et al, 1993; Jerome et al, 2006a, b; Barkley and Cox, 2007; Merkel et al, 2013). Though less often discussed, motor impairments are prominent among children with ADHD (Barkley, 1998) and up to 50% of pediatric ADHD patients are also comorbid for developmental coordination disorder (Kadesjo and Gillberg, 1999; Pitcher et al, 2003; Gillberg et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…; DSM-5 ; American Psychiatric Association [APA], 2013) replaced the term “subtypes” with “presentations” to reflect the observation that symptoms can manifest differently over time. As individuals with ADHD become older, symptoms can decrease in severity, with inattentive symptoms generally being more persistent than hyperactive-impulsive symptoms (Turgay et al, 2012; Wilens et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Although ADHD is often described as a childhood disorder, and can remit over time, ADHD symptoms persist into adulthood in about two thirds of cases, with associated impairment across multiple domains (Biederman, Petty, Evans, Small, & Faraone, 2010; Faraone, Biederman, & Mick, 2006; Turgay et al, 2012). Previous research has identified several risk factors for the persistence of childhood ADHD into adulthood: a family history of ADHD (Biederman et al, 1996; Biederman et al, 2010; Biederman, Petty, O’Connor, Hyder, & Faraone, 2012), ADHD symptom severity and associated impairment (Biederman, Petty, Clarke, Lomedico, & Faraone, 2011; Kessler et al, 2005; Lara et al, 2009), and comorbidity with conduct, oppositional defiant, mood, and anxiety disorders (Biederman et al, 1996; Biederman et al, 2011; Biederman et al, 2010; Biederman et al, 2012; Lara et al, 2009).…”
Section: Introductionmentioning
confidence: 99%